L’Autorité et l’autre, parcours toponymiques et méandres linguistiques au Québec - Francine Adam (L'Espace Politique, 2008)
Place names in Quebec stem from three main origins: the native, French and English languages. Along history, these three sources have been diversely combined, according to the geopolitical context in which were established the relations between the cultures which they represented, particularly after these relations were embodied by the Geographical Commission (1912) and the Commission de toponymie (1977). Following the course of history, place names were changed or deleted, expressing political and territorial dynamics through the successive moves of neotoponymical frontiers. Contemporary neotoponymy is variegated and fraught with self-asserting cultural choices. The Commission de toponymie du Québec, which was created nine months after the Parti Québécois acceded to power, greatly contributed to these changes, e.g. by replacing French and English place names with native ones in Northern Quebec, launching a program for adopting new names commemorating the past, creating names as custodians of tradition and cultural heritage, etc. For their part, the highest governmental authorities have created a neotoponymical context by implementing a project of municipal and territorial mergers (2001). For instance, the merger of Métabetchouan and Lac-à-la-Croix initiated a reflection about the links between names, places and politics.